(untitled) (Research, Society and Development, 2020)
With the advancement of medicine, the vaccine against human papillomavirus (HPV) was developed. HPV is a sexually transmitted virus and the vaccine is a skillful means of preventing transmission. However, the vaccine needs to be applied to the at-risk population, young women and men. Therefore, the objective of the present study is to highlight comprehensive studies on the applicability of the vaccine to the population in an efficient manner. The research will approach a wide review of scientific articles published in recent years, the collection will be carried out in the Google Scholar Database, MEDLINE and SciELO, allowing a discourse analysis of the selected works, and thus, building a critical analysis resulting from the information gathered about the population at risk, effectiveness and stigmas of non-vaccination. In a critical analysis, it was corroborated that although vaccination has proven to be effective, the population at risk is not totally immune to the virus, since the stigmas imposed by contemporary society end up preventing vaccination from happening in 100% of the population. Thus, the study confirmed the need for permanent prevention policies in health units that aim at health education so that vaccination can reach the entire population at risk.